Fracture behavior in electrically poled alkaline bismuth- and potassium- based lead-free piezoceramics using Vickers indentation. (15th March 2021) - Wang, Xueyao; Venkataraman, Lalitha Kodumudi; Tan, Chi; Li, Yingwei
Abstract: The fracture behavior of unpoled and electrically poled Ka0.5 Na0.5 NbO3 (KNN)- and Na1/2 Bi1/2 TiO3 (NBT)- based lead-free piezoceramics were characterized using the Vicker's indentation technique and compared with soft Pb(Zr, Ti)O3 piezoceramics. In the unpoled state, NBT-based piezoceramics demonstrate the largest fracture toughness in comparison with KNN-based and soft PZT piezoceramics due to its large intrinsic fracture toughness, which is in accordance with the previous reports. In the electrically poled state, KNN- and NBT- based piezoceramics exhibit large fracture toughness along the poling direction as opposed to perpendicular to the poling direction, with aspect ratios of 1.2 and 1.1, significantly smaller than that for PZT (1.8). The variations of the remanent strain and the process zone, which are related to the texture and the material properties during crack propagation were used to rationalize the results. Graphical abstract: Image, graphical abstract